Leveraging value in multi-stakeholder innovation networks: A process framework for value co-creation and capture - Reypens, Charlotte; Lievens, Annouk; Blazevic, Vera (Industrial marketing management, 2016)
To develop innovative solutions for complex societal and scientific challenges, organizations need to move beyond the boundaries of single firms and engage in collaborative networks. In these networks, multiple, diverse stakeholders are working together to co-create innovative value. Co-creation in a network creates new challenges in terms of changed processes and outcomes. Guided by grounded theory methodology, we explore these aspects by studying a public–private partnership involving 57 stakeholders. We take the number and diversity of stakeholders into account to shed light on the distinct processes through which value is co-created and captured. We also identify the types of value outcomes that accrue to the network and its participants. Overall, we present a multi-level cyclical process framework for leveraging value in multi-stakeholder collaborations and visualize these collaborations as a value space in which all stakeholders are uniquely positioned. In doing so, this study provides novel insights into the systemic, multi-actor nature of value co-creation and supports collaborators in maximizing value for both individual stakeholders and the network as a whole.